CRITICAL REVIEW OF ETHNOGRAPHIC APPROACH - Lusia Marliana Nurani (Fakultas Seni Rupa dan Desain ITB, 2008)
There are two basic characteristics of ethnography: (1) the observation takes place in natural setting, (2) researchers must understand how an event is perceived and interpreted by the people in a speech community. In other words, the researchers try to interpret the situation being observed from the perspective of the participants. Ethnography also relies on observations of interactions and interviews with participants in naturally occurring situation. The next characteristic of ethnography is the characteristic of